Folate promotion in Western Australia and the prevention of neural tube defects - Carol Bower; Margaret Miller; Jan Payne; Peta Serna; Nicholas deKlerk; Fiona J. Stanley (Elsevier, 2004)
Abstract Objectives: We conducted a case‐control study to investigate the effectiveness of efforts to increase folate intake in Western Australia (WA) for the prevention of neural tube defects (NTD). Methods:Case (36) and control (578) mothers completed questionnaires, from which their intake of folate from supplements and food (including fortified foods) was estimated. Results:Almost one‐third of women took folic acid supplements periconceptionally. Supplement use was associated with a non‐significant 4% reduction in risk. For women not taking supplements, dietary sources of folate were protective, and most women obtained at least some folate from fortified food. Conclusions: For the two‐thirds of WA women not taking supplements, fortified food is an important source of folate for the prevention of NTD. Implications: Greater promotion of foods currently allowed to be fortified with folate, or mandatory fortification, is needed to maximise prevention of NTD in Australia.